2008
DOI: 10.1177/0269881108096507
|View full text |Cite
|
Sign up to set email alerts
|

Better sexual acceptability of agomelatine (25 and 50 mg) compared with paroxetine (20 mg) in healthy male volunteers. An 8-week, placebo-controlled study using the PRSEXDQ-SALSEX scale

Abstract: Sexual dysfunction (SD) is a common and underestimated effect of antidepressants. Healthy volunteers are the most adequate group to study this adverse event avoiding influence of depression itself. Sexual acceptability of agomelatine (a melatonergic agonist and 5HT(2C) antagonist) paroxetine and placebo by using the Psychotropic-Related Sexual Dysfunction Salamanca Sex Questionnaire (PRSEXDQ-SALSEX) was explored. A total of 92 healthy male volunteers were randomised to agomelatine (25 or 50 mg), paroxetine 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 36 publications
10
59
0
2
Order By: Relevance
“…Some novel antidepressants may have a relatively low propensity for adverse effects on sexual function 73 . Randomized controlled trials with agomelatine suggest it has fewer adverse effects on sexual functioning than some other antidepressants, which is probably due to its antagonist effects at the 5-HT2C receptor, rather than the agonist effects at melatonin receptors [74][75][76][77] , although the absence of effects on nitrergic relaxation of corpus cavernosum smooth muscle may also be relevant 78 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…Some novel antidepressants may have a relatively low propensity for adverse effects on sexual function 73 . Randomized controlled trials with agomelatine suggest it has fewer adverse effects on sexual functioning than some other antidepressants, which is probably due to its antagonist effects at the 5-HT2C receptor, rather than the agonist effects at melatonin receptors [74][75][76][77] , although the absence of effects on nitrergic relaxation of corpus cavernosum smooth muscle may also be relevant 78 .…”
Section: Influence Of Treatment Of Depression On Sexualitymentioning
confidence: 99%
“…During a 6-month period, relapse was significantly lower in patients on continued agomelatine therapy compared to placebo (Goodwin et al, 2009). Additionally, this drug has less sexual side effects than SSRIs (Montejo et al, 2010). However, problematic are the transient elevations in liver enzymes, which is one reason why agomelatine is not approved for use in the US.…”
Section: Agomelatinementioning
confidence: 99%
“…This was borne out in an eight-week, placebo-controlled study in healthy volunteers, that revealed that sexual dysfunction was significantly lower in those taking agomelatine, compared to those taking paroxetine. 41 In a 12-week study in depressed patients, agomelatine showed a superior sexual side-effect profile compared to venlafaxine. 23 Transient and mild nausea and dizziness are the most common adverse reactions, and these usually occur in the first two weeks and generally do not lead to cessation of treatment.…”
Section: S Afr Fam Pract 2012mentioning
confidence: 99%